Evaluation of Young Surgeon’s Experience and Outcomes in Endoscopic Tympanoplasty Surgery - Ali Say, Mehmet; Verim, Ayşegül; Kılıç, Murat; Aybal, Alperen (ENT Updates, 2024)
Background: Rigid telescopes, which provide wider surgical feld imaging, improved resolution, and high magnifcation capabilities, have recently found widespread use in ear surgery. This study aimed to review the outcomes and duration of operations in endoscopic transcanal tympanoplasty and to guide surgeons who have just started endoscopic ear surgery (EES). Methods: This study included 47 outpatient or inpatient volunteers who underwent endoscopic transcanal tympanoplasty surgery at the Otolaryngology clinic between March 2021 and March 2023. The age and sex of the patients, the surgery duration, and the side of the operated ear were reviewed. The first 23 operated patients were compared with the last 24 operated patients in terms of the duration of the operation. Postoperative graft success (anatomical success) in the patients at 6 months was reviewed. Hearing gain in patients was examined postoperatively at 6 months using an audiometry test with hearing thresholds at 0.5, 1, 2, and 4 kHz. Results: Upon examination of the patients at 6 months, the graft success was 89.4%. There was a statistically signifcant recovery in all 4 frequencies based on the preoperative and postoperative hearing tests (P=.00). There was a signifcant decrease in the duration of the operation in patients who were operated in the later stages of the study (P=.00). Conclusion: Although there is a learning curve associated with EES, this type of operation is based on team effort, and the surgery duration decreases over time, with the experience acquired by each healthcare provider included in the team.